2022
DOI: 10.3390/cancers14184519
|View full text |Cite
|
Sign up to set email alerts
|

How I Treat TP53-Mutated Acute Myeloid Leukemia and Myelodysplastic Syndromes

Abstract: TP53-mutated acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) are among the myeloid malignancies with the poorest prognosis. In this review, we analyze the prognosis of these two diseases, focussing particularly on the extent of the mono or biallelic mutation status of TP53 mutation, which is largely correlated with cytogenetic complexity. We discuss the possible/potential improvement in outcome based on recent results obtained with new drugs (especially eprenetapopt and magrolimab). We also fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Moreover, TP53-mutated MDS and AML cases are associated with a poor median overall survival, typically ranging from 5 to 10 months. 18 AML with TP53 mutations often exhibit more aggressive disease behaviour, increased resistance to chemotherapy and a higher rate of relapse than other types. In patients with TP53 mutations, VEN + AZA was thought to be associated with better remission rates but not improved survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TP53-mutated MDS and AML cases are associated with a poor median overall survival, typically ranging from 5 to 10 months. 18 AML with TP53 mutations often exhibit more aggressive disease behaviour, increased resistance to chemotherapy and a higher rate of relapse than other types. In patients with TP53 mutations, VEN + AZA was thought to be associated with better remission rates but not improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…TP53‐mutated MDS and AML exhibit significantly lower response rates to induction chemotherapy, hypomethylating agent‐based regimens or VEN‐based therapies when compared to TP53‐wild patients. Moreover, TP53‐mutated MDS and AML cases are associated with a poor median overall survival, typically ranging from 5 to 10 months 18 . AML with TP53 mutations often exhibit more aggressive disease behaviour, increased resistance to chemotherapy and a higher rate of relapse than other types.…”
Section: Discussionmentioning
confidence: 99%
“…88 In TP53-mutated AML patients who achieve CR with intensive chemotherapy, allo-HSCT is recommended but is still associated with a high relapse risk and poor outcome. 89,90 TP53-altered MDS with excess blasts (5%-19%) (MDS-EB) and TP53-altered AML show overlapping clinical outcomes, independently by the treatment received, including intensive chemotherapy, hypomethylating agents, venetoclax-based regimens 46,91 and allogeneic stem cell transplantation. 36,92 Thus, it has been suggested that TP53altered AML/MDS-EB should be approached as a single entity in clinical trials.…”
Section: Aml With Recurrent Genetic Abnormalitiesmentioning
confidence: 99%
“…AML patients with mutated TP53 and poor risk cytogenetic who are unfit for chemotherapy do not benefit from the addition of venetoclax to azacytidine, in terms of duration of remission and overall survival 88 . In TP53 ‐mutated AML patients who achieve CR with intensive chemotherapy, allo‐HSCT is recommended but is still associated with a high relapse risk and poor outcome 89,90 …”
Section: Acute Myeloid Leukemiasmentioning
confidence: 99%
“…TP53 Mutated R/R AML Patients with AML and a TP53 mutation have a poor prognosis, irrespective of the treatment administered, including after allogeneic HSCT [97]. TP53 mutations are found in about 5-15% of patients with ND-AML, but Non-Immunotherapy for Advanced Leukemia Acta Haematol 2024;147:160-175 DOI: 10.1159/000534897 may occur in up to 25% of cases in elderly individuals [98].…”
Section: Special Clinical Scenariosmentioning
confidence: 99%